2020
DOI: 10.1136/bmj.m236
|View full text |Cite
|
Sign up to set email alerts
|

China coronavirus: cases surge as official admits human to human transmission

Abstract: More than 200 confirmed cases of infection with the novel coronavirus have emerged in China, including three deaths and cases outside the city of Wuhan, in central Hubei province, where it was first identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 1 publication
0
78
0
3
Order By: Relevance
“…The 2019-nCoV is a novel coronavirus, which is different from SARS and other SARS-like viruses (3). However the time-varying transmission dynamics of NCP during the epidemic remain unclear (22). In this study, we estimated the R0 of NCP infected with 2019-nCoV nationwide, and found that the R0 was 4.5, which means an average of 4.5 secondary cases generated by a primary case in the early stage.…”
Section: Discussionmentioning
confidence: 88%
“…The 2019-nCoV is a novel coronavirus, which is different from SARS and other SARS-like viruses (3). However the time-varying transmission dynamics of NCP during the epidemic remain unclear (22). In this study, we estimated the R0 of NCP infected with 2019-nCoV nationwide, and found that the R0 was 4.5, which means an average of 4.5 secondary cases generated by a primary case in the early stage.…”
Section: Discussionmentioning
confidence: 88%
“…The human to the human spreading of the virus occurs due to close contact with an infected person, exposed to coughing, sneezing, respiratory droplets or aerosols. These aerosols can penetrate the human body (lungs) via inhalation through the nose or mouth (Fig 2) ( [11][12][13][14].…”
Section: Comparative Analysis Of Emergence and Spreading Of Coronavirmentioning
confidence: 99%
“…As of 7 pm Central European Time on 24 March, 2020, 407,485 cases of pneumonia had been reported globally [1,2,3] that were caused by the novel coronavirus that is now known as COVID-19 [4]. 18,227 cases have resulted in death [5]. There have been 325,894 reported cases in other 184 countries and territories, including Italy (n=69,176), Iran (n=24,811) and South Korea (n=9,037) [6,7].…”
Section: Introductionmentioning
confidence: 99%